(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Water shortage, inefficient consumption habits, fast worldwide population growth, a high demand-to-production ratio, and a slew of other issues underscore the urgent need to systematically acquire and use alternative, and, most critically, renewable water supply options. In addition, the use of well-designed and maintained rainwater harvesting systems in the built environment while expanding the focus to a variety of building typologies is advocated as a possible solution to these systemic problems. In developing and green building environments, there is a gap in the effective integration of these design elements to achieve consistent sustainable results in maintenance plans. Governments are urged to play an important role in the education, opportunity creation and support of these decentralized water supply and consumption systems. as meetings, the potential to properly merge them with green roofs and green building environmental criteria, and finally manipulated government regulations to provide information to overcome the above mentioned problem of intensification of rainfall.